2015
DOI: 10.1007/s10488-015-0649-6
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Relevance of Routinely Collected Outcome Data for Mental Health Care Decision Making

Abstract: Evidence shows that routine outcome monitoring (ROM) and feedback using standardized measurement tools enhances the outcomes of individual patients. When outcome data from a large number of patients and clinicians are collected, patterns can be tracked and comparisons can be made at multiple levels. Variability in skills and outcomes among clinicians and service settings has been documented, and the relevance of ROM for decision making is rapidly expanding alongside the transforming health care landscape. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Over recent years, the importance of capturing the client perspective has been acknowledged (5). ROM data is important for treatment planning and quality assurance (6-9) and allows organisations to understand, evaluate and improve service delivery (9,10). From a research perspective, ROM data provides insight into which clients receive the most benefit from services and how variations in care may impact engagement and outcomes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, the importance of capturing the client perspective has been acknowledged (5). ROM data is important for treatment planning and quality assurance (6-9) and allows organisations to understand, evaluate and improve service delivery (9,10). From a research perspective, ROM data provides insight into which clients receive the most benefit from services and how variations in care may impact engagement and outcomes (9).…”
Section: Introductionmentioning
confidence: 99%
“…Patients have difficulty selecting mental health providers (Boswell, Constantino, Kraus, Bugatti & Oswald, ) and other healthcare providers. With the movement toward measurement‐based care (MBC), the role of routine outcomes monitoring (ROM) data is likely to increase over time in managing care (Boswell & Constantino, ) and it remains to be seen how consumers’ interest and confidence in using such data to select providers will evolve.…”
Section: Board Certification Benefits Consumersmentioning
confidence: 99%
“…A wide body of research has demonstrated that when ROM is used consistently, frequently enough, in a digestible way, and in a timely fashion with psychometrically sound standardized measurement tools, it has potential to improve many facets of patient care, including communication between providers and patients, provider diagnostic ability, treatment planning, progress monitoring, symptom reduction, outcome effect size, detection of deterioration, patient engagement, and patient retention 2‐26 . Moreover, on a clinic level, ROM can be used to evaluate treatment effectiveness, identify patterns among providers and patients, develop innovative population‐based treatments, and inform decision making on allocation of resources 27 . Since 2018, these findings have led the Joint Commission on Accreditation of Healthcare Organizations ( JCAHO ) to mandate that behavioural health organizations gather feedback derived through standardized instruments to inform individual‐level patient treatment and organizational performance improvement efforts 28…”
Section: Introductionmentioning
confidence: 99%